Acanthamoeba Keratitis Diagnosis and Treatment - Sun, Xuguang (Springer Singapore, 2018)
This book provides the concise descriptions of the basic and clinical knowledge about Acanthamoba keratitis, including characteristics of pathogen, risk factors, clinical manifestations, diagnosis and treatment with abundant figure illustrations and typical cases to ophthalmological practitioners and researchers. Acanthamoeba pathogen is widely distributed in the nature. However, Acanthamoeba keratitis is generally considered as a type of sight-threatening keratitis that is difficult to treat. At early stage Acanthamoeba keratitis usually shows atypical clinical manifestations, that are often misdiagnosed as viral or bacterial keratitis. Moreover, there are not approved topical anti-amoebicdrugs available up to now. We hope ophthalmological practitioners can obtain a comprehensive understanding of this infection through this book. Xuguang Sun is a professor of Ophthalmology at Beijing Institute of Ophthalmology, Beijing Tongren Eye Center, Beijing Tongren Hospital, Capital Medical University, Beijing, China.